NaIO4-KI-NaN3 as a new reagent system for C-H functionalization in hydrocarbons - Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2008)
The NaIO4-KI-NaN3 combination has been found to be an efficient, reliable, and inexpensive reagent system for mono- and 1,2-difunctionalization of hydrocarbons via C-H bond activation to afford vicinal azido- and acetoxy iodinations of cyclic hydrocarbons. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: azides; C-H activation; Iodination; NaIO4

NaIO4/LiBr-mediated aziridination of olefins using chloramine-T - Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Shaikh, Tanveer M.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A new milder protocol for aziridination of a variety of olefins has been described. The process employs catalytic amount of sodium metaperiodate (NaIO4) as an oxidant and LiBr and chloramine-T as the bromine and nitrogen sources, respectively. Interestingly, the formation of aziridine products in all the cases studied takes place presumably through a process of 1,2-aminobromination of alkenes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aziridination; Chloramine-T; Lithium bromide; Olefin; Sodium metaperiodate

NaIO4-NaN3-mediated diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones - Kamble, Dayanand A.; Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Sodium periodate and sodium azide combination has been found to be an excellent reagent system suitable for the direct diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones to produce the corresponding vicinal and geminal diazides respectively in high yields under mild reaction conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: alkenes; Aryl ketones; Geminal diazides; Sodium periodate; Vicinal diazides